Endovascular treatment of isolated arterial pulmonary malinosculation - Mammen, Suraj (Indian J Radiol Imaging, 2015)
We report the endovascular management of a series of four cases of isolated systemic supply to normal lung or isolated arterial pulmonary malinosculation of the left lung. In these cases, the basal segments of the left lung lacked normal pulmonary arterial supply and instead received systemic arterial blood from the descending thoracic aorta. The relevant anatomy and literature are also reviewed.